Determination of prevalence and antibiotic susceptibility pattern of the bacterial isolates collected from different parts of domestic refrigerators - Hasan, Fatema Raad (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2018.